Hydrophobic Interface-assisted protein crystallization: theory and experiment - Nanev,C; Saridakis,E; Govada,L; Kassen,SC; Solomon,HV; Chayen,NE (ACS Applied Materials and Interfaces, 2019)
Macromolecular crystallization is crucially important to a large number of scientific fields, including structural biology, drug design, formulation and delivery, the manufacture of biomaterials, and the preparation of foodstuffs. The purpose of this study is to facilitate control of crystallization, by investigating hydrophobic interface-assisted protein crystallization both theoretically and experimentally. The application of hydrophobic liquids as nucleation promoters or suppressors has rarely been investigated, and provides an underused avenue to explore in protein crystallization. Theoretically, crystal nucleation is regarded as a two-step process, the first step being a local increase in protein concentration due to its adsorption on the hydrophobic surface. Subsequently, the protein is ordered in a crystal lattice. The energetic aspect of crystal nucleation on water/hydrophobic substance interfaces is approached by calculating the balance between the cohesive energy maintaining integrity of the 2D-crystal nucleus and the sum of destructive energies tending to tear up the crystal. This is achieved by comparing the number of bonds shared by the units forming the crystal and the number of unshared (dangling) bonds on the crystal surface pointing toward the solution. The same approach is extended to 3D protein crystal nucleation at water/hydrophobic liquid interfaces. Experimentally, we studied protein crystalliza-tion over oils and other hydrophobic liquids (paraffin oil, FC-70 Fluorinert fluorinated oil, and three chlorinated hydrocarbons). Crystallization of α-lactalbumin and lysozyme are compared, and additional information is acquired by studying α-crustacyanin, trypsin, an insulin analogue and protein Lpg2936. Depending on the protein type, concentration, and the interface aging time, the proteins exhibit different crystallization propensities depending on the hydrophobic liquid used. Some hydrophobic liquids provoke an increase in the effective